Difference of immune cell infiltration between stable and unstable carotid artery atherosclerosis. Issue 23 (3rd November 2021) - Gao, Jia; Shi, Licheng; Gu, Jianhua; Zhang, Dandan; Wang, Wenjun; Zhu, Xuanfeng; Liu, Jiannan
Abstract: Atherosclerotic plaque instability contributes to ischaemic stroke and myocardial infarction. This study is to compare the abundance and difference of immune cell subtypes within unstable atherosclerotic tissues. CIBERSORT was used to speculate the proportions of 22 immune cell types based on a microarray of atherosclerotic carotid artery samples. R software was utilized to illustrate the bar plot, heat map and vioplot. The immune cell landscape in atherosclerosis was diverse, dominated by M2 macrophages, M0 macrophages, resting CD4 memory T cells and CD8 T cells. There was a significant difference in resting CD4 memory T cells ( p = 0.032), T cells follicular helper ( p = 0.033), M0 ( p = 0.047) and M2 macrophages ( p = 0.012) between stable and unstable atherosclerotic plaques. Compared with stable atherosclerotic plaques, unstable atherosclerotic plaques had a higher percentage of M2 macrophages. Moreover, correlation analysis indicated that the percentage of naïve CD4 T cells was strongly correlated with that of gamma delta T cells ( r = 0.93, p < 0.001), while memory B cells were correlated with plasma cells ( r = 0.85, p < 0.001). In summary, our study explored the abundance and difference of specific immune cell subgroups at unstable plaques, which would aid new immunotherapies for atherosclerosis.